Designing with multiple perspectives: an interactive learning environment for developing systems thinking in a carbon cycle context - Mani, Mina; Gezelius, Måns; Löwgren, Jonas; Höst, Gunnar; Koć-Januchta, Marta M.; Tibell, Lena A. E.; Schönborn, Konrad J. (Interactive learning environments, 2025)
Although there is an increasing body of knowledge on interactive learning environments in science education, there is little reported on the empirical process of designing such environments with multiple perspectives. This study describes the design of Tracing Carbon, a learning environment for developing grade 7-9 pupils' systems thinking skills in the context of the carbon cycle. Following an educational design research approach, we describe an explorative iterative design process that integrates multiple perspectives, including conceptual drivers, the design team, science teachers, and pupils. The design process resulted in an adaptive interactive visual learning environment with multiple learning tasks and quizzes organised in three modules addressing ecological, global and human intervention-related aspects of the carbon cycle. Each module is designed with coherent learning objectives aligned with a systems thinking skills hierarchy and the Swedish school curriculum. Our main insights concern the applicability of the systems thinking hierarchical model, the didactic value of adaptive and interactive visual learning tasks, and the contributions of professional teachers to going beyond established interaction design conventions. These findings might guide the development of interactive learning environments for other science learning situations. Future work will investigate the integration of Tracing Carbon in science teaching in schools.